Pengaruh Leverage Dan Profitabilitas Terhadap Transfer Pricing Pada Perusahaan Manufaktur Sub Sektor Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia Tahun 2019 – 2023 - Enyvia Natania Siagian; Hasbiana Dalimunthe (VALUE, 2024)
The aim of this research is to examine the impact of leverage and profitability on transfer pricing through various food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the period 2019 - 2023. Researchers used quantitative techniques in this research using secondary data. Purposive sampling is a technique used by researchers in the sampling stage. The analytical method used is multiple linear regression on 11 food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange during the 2019 - 2023 period. The research results obtained show that leverage partially has a negative and unidirectional influence on transfer pricing, while profitability has a positive and significant influence on transfer pricing. Simultaneously, leverage and profitability have a good or positive and significant impact on transfer pricing